CONCRETE WITH CRUSHED COCONUT SHELL AS COARSE AGGREGATE - Dahiya, Himanshu; Dharni, Naveen (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The high cost of conventional building materials is a major factor affecting housing delivery in world. This has necessitated research into alternative materials of construction and analyzing flexural and compressive strength characteristics of concrete produced using crushed, granular coconut as substitutes for conventional coarse aggregate with full replacement using M25 grade concrete. The main objective is to encourage the use of these ‘seemingly’ waste products as construction materials in low-cost housing. It is also expected to serve the purpose of encouraging housing developers in investing these materials in house construction. This project paper aims at analyzing the compressive strength characteristics of concrete produced using crushed, granular coconut as coarse aggregate with partial replacement using M25 grade concrete. Cubes are casted, tested and their properties are determined in this paper